PENDAMPINGAN SOSIALISASI ZAKAT SECARA SOSIAL-TRANSFORMATIF PERSPEKTIF AL-QUR’AN DI MAJLIS TA’LIM MUSLIMAT, BEKASI - Ali Nurdin; Ahmad Zulki; Ulfia Ningrum; Muhammad Hariyadi; Ahmad Berizi; Ceceng Mumu Muhajirin (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This study examines Masdar Farid Mas’udi’s concept of transformative exegesis, particularly his reconstruction of zakat as a social justice instrument that can be integrated into the national taxation system. Employing a contextual and maqâṣid al-sharî‘ah-based approach, Masdar challenges the ritualistic view of zakat and proposes its reinterpretation as a structural mechanism for equitable wealth distribution. This study uses a qualitative method through literature review, analyzing Masdar’s works and relevant scholarly sources. The findings suggest that a transformative understanding of zakat provides a promising path for renewing Islamic legal thought in ways that uphold the core values of the sharia while remaining responsive to contemporary socio-economic realities. Masdar’s framework offers a constructive bridge between religious texts and public policy grounded in social justice